1987
DOI: 10.3354/dao003013
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of the chronic soft-shell syndrome in the tiger prawn Penaeus mondon

Abstract: One of the disease problems that affect the production of tiger prawn Penaeus monodon Fabricius in brackish-water ponds is the chronic soft-shell syndrome, a condition in which the prawn shell is persistently soft for several weeks. To determine the extent of damage in affected prawns, the histopathology of this syndrome was studied using light microscopy, transmission and scanning electron microscopy, and histochemical determination of calcium. Light microscopic studies of the exoskeleton of soft and normal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…General atrophy of tubules and reduction in the level of lipid storage in the HP cells as 169 Day LSS inoculum Control noticed in the present study has also been reported in the American lobster Homarus americanus subjected to nutritional stress (Rosemark et al 1980). Similarly, in shrimp affected by soft shell syndrome, the HP tubules were compressed, disarranged, and disrupted, and the lumen appeared to be larger because of the breakdown of secretory cells (Baticados et al 1987). …”
Section: Discussionsupporting
confidence: 58%
“…General atrophy of tubules and reduction in the level of lipid storage in the HP cells as 169 Day LSS inoculum Control noticed in the present study has also been reported in the American lobster Homarus americanus subjected to nutritional stress (Rosemark et al 1980). Similarly, in shrimp affected by soft shell syndrome, the HP tubules were compressed, disarranged, and disrupted, and the lumen appeared to be larger because of the breakdown of secretory cells (Baticados et al 1987). …”
Section: Discussionsupporting
confidence: 58%
“…The presence of Vibrio species in shrimp grow-out ponds can be attributed to multiple etiological agents (Raja et al 2012). Several studies reported that nutritionally imbalanced shrimp feed, susceptibility to different chemical pesticides, deterioration of pond soil and water quality, and poor management practices can be responsible for LSSD in shrimps (Baticados et al 1986). We recorded 100% mortality due to intramuscularly inoculated LSSD-affected shrimp extracts in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Other symptoms include loss of appetite, weak response to stimuli, and erratic swimming (Loka et al 2012). The occurrence of LSSD in a shrimp farm is believed to be associated with such factors as nutritionally imbalanced feed, different chemical pesticides, deterioration of pond soil and water quality, and poor management practices (Baticados et al 1986). The onset of LSSD in shrimp farms can be easily detected by changes in the exoskeleton as well as in the internal organs.…”
Section: Introductionmentioning
confidence: 99%
“…[11] observed the reason for the LSS infection due to the factors such as nutritional deficiency, pesticide pollution and poor water quality and certain management practices.…”
Section: Discussionmentioning
confidence: 99%